2006
DOI: 10.1016/j.wasman.2005.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of temperature and thermal inertia effect in the maturation stage and stockpiling of a large composting mass

Abstract: A macroscopic non-steady state energy balance was developed and solved for a composting pile of source-selected organic fraction of municipal solid waste during the maturation stage (13500 kg of compost). Simulated temperature profiles correlated well with temperature experimental data (ranging from 50 to 70ºC) obtained during the maturation process for more than 50 days at full scale. Thermal inertia effect usually found in composting plants and associated to the stockpiling of large composting masses could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…However, recent results obtained in the industrial composting of municipal solid wastes have shown that the utilization of large particles of bulking agent used to prevent a loss of porosity in large composting masses does not have a significant effect on the material heat retention. In these organic wastes, the temperature is maintained for long periods given the properties of compost as a heat insulator (Barrena et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent results obtained in the industrial composting of municipal solid wastes have shown that the utilization of large particles of bulking agent used to prevent a loss of porosity in large composting masses does not have a significant effect on the material heat retention. In these organic wastes, the temperature is maintained for long periods given the properties of compost as a heat insulator (Barrena et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…For mixture 3 no differences in the biological activity were observed through the process. The measurement of biological activity is of special relevance in full scale facilities, where the temperature is maintained in the thermophilic range because of the limited heat transfer (Barrena et al, 2006b), even when biological activity has diminished. Differences were observed in the evolution of interstitial oxygen content of the studied materials.…”
Section: Composting Experiments At Full Scale (Our Insitu )mentioning
confidence: 99%
“…Indeed, during waste composting the high temperatures reached strongly affect the microbial growth and biodegradation kinetics [9]. The high values are directly influenced by the mode and frequency of aeration [10][11][12] as well as the compost's insulating properties [13].…”
Section: Introductionmentioning
confidence: 99%